Superior mesenteric artery first approach can improve the clinical outcomes of pancreaticoduodenectomy: A meta-analysis. (January 2020) - Jiang, Xiangyan; Yu, Zeyuan; Ma, Zhijian; Deng, Haixiao; Ren, Wen; Shi, Wengui; Jiao, Zuoyi
Abstract: Background and aim: Superior mesenteric artery (SMA) first approach was a new improvement for pancreaticoduodenectomy (PD), but there is no evidence whether this approach is advantageous to PD. This meta-analysis aimed to determine the effects of the superior mesenteric artery (SMA) first approach on outcomes of pancreaticoduodenectomy (PD). Methods: Literature searches were conducted on PubMed, The Cochrane Library, EMBASE, Web of Science, Clinical Trials Registry and China Biology Medicine disc. We completed a meta-analysis of the SMA first approach in PD, assessing overall survival, R0 resection, blood loss, postoperative complications, operation time and postoperative stay. The odds ratios and weighted mean differences with 95% confidence intervals (CIs) were pooled. Results: Eighteen studies comprising 1483 participants were included. Patients who received SMA-PD had significantly lower overall complication rate (OR 0.62, 95% CI 0.47 to 0.81, P = 0.001) and less blood loss (WMD -264.84, 95% CI -336.1 to −193.58, P < 0.001). The obviously increased R0 resection rate (OR 2.92, 95% CI 1.72 to 4.96, P < 0.001) and 3-year OS (OR 2.15, 95% CI 1.34 to 3.43, P = 0.001) were found in the SMA-PD group. Conclusion: The SMA-PD group had better clinical outcomes, particularly in long-term survival of pancreatic cancer patients; furthermore, the patients acquired superior clinical efficacy via the posterior approach in SMA-PD. Highlights: Operative efficacy was different between six SMA approaches, and the posterior approach exerted the optimal clinical outcomes. The SMA approach appears remarkable advantages for achievement of R0 resection and reduction of blood loss. The SMA group had better clinical outcomes, particularly in long-term survival of pancreatic cancer patients.